Relationship between bmi and glomerular filtration rate in a large cohort initiating a weight loss program: differential contributions of fat mass, fat-free mass, and abdominal fat compartments - Leone, Alessandro; Menichetti, Francesca; Vignati, Laila; Sileo, Federica; De Amicis, Ramona; Foppiani, Andrea; Bertoli, Simona; Battezzati, Alberto (Nutrition journal, 2025)
Background The relationship between BMI and chronic kidney disease is controversial, likely due to the inability of BMI to accurately define body composition and adipose tissue distribution. Our objective was to evaluate the synergistic contribution of fat-free mass, fat mass, visceral (VAT) and subcutaneous (SAT) adipose tissue, to glomerular filtration rate (GFR) in a large cohort of subjects. Methods A cross-sectional study of 9704 subjects (72% female, median age 47y, median BMI 28.1 kg/m 2 ) was carried out. Each patient underwent an anthropometric assessment (weight, height, waist circumference, % of body fat by body skinfolds), an ultrasound measurement of VAT and SAT and blood sampling to measure metabolic syndrome (MS) parameters and serum creatinine. GFR was estimated using the EPI-CKD equation. MS was defined according to the harmonized criteria. Results Among 9,704 subjects, 61.1% had a normal renal function, while 29.3% reported a reduction, from slightly to severely. The BMI was initially negatively associated with GFR in the univariate model (β = -0.32, 95% CI: -0.39, -0.25), but after adjusting for %body fat, the association was lost. We then split the BMI into its two components, Fat Mass Index (FMI) and Fat Free Mass Index (FFMI), and observed that FMI (β = -1.23, 95% CI: -1.35, -1.12) and FFMI (β = 0.79, 95% CI: 0.65, 0.92) were associated with a decrease and an increase in GFR, respectively. VAT (β = -1.83, 95% CI: -2.00, -1.67) and SAT (β = 3.21, 95% CI: 2.86, 3.57) were independently associated with a decrease and an increase in GFR, respectively. Similar results were obtained when studying the association between BMI, body composition, adipose tissue distribution, and the risk of reduced GFR (<90 ml/min/1.73 m 2 ). Stratification by sex and MS did not substantially alter the results. A significant association between VAT and reduced GFR was observed only in women. Conclusions Our study highlights the importance of considering body composition and fat distribution when assessing renal function.